2019
DOI: 10.1111/ajt.15154
|View full text |Cite
|
Sign up to set email alerts
|

Variability in endocrine cell identity in patients with chronic pancreatitis undergoing islet autotransplantation

Abstract: | INTRODUC TI ONChronic pancreatitis (CP) is an inflammatory disease characterized by progressive fibrosis of the pancreatic parenchyma, and is associated with islet damage and glucose dysregulation. Pancreatectomy and islet autotransplantation (PIAT) is a treatment for this disease.Endocrine dedifferentiation is an incompletely understood process, with emerging evidence that β-cells are not only lost by apoptosis in response to chronic hyperglycemia, but they also dedifferentiate, which contributes to subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…All patients were non-diabetic at the time of transplant, and all received equivalent numbers of islets (~5000 IE/kg). Using histological markers of β-cell identity including hormones, vimentin, synaptophysin, Ucn3, and MafA, we found that β-cell dedifferentiation was evident in all patients undergoing PIAT, which paralleled disease severity, and could be stratified relative to ND control and T2DM control donor samples [128]. These findings were further supported by pre-and postsurgical metabolic function tests, HbA 1C , and GSIS assessments with up to 4 years follow-up.…”
Section: Endocrine Cell Dedifferentiation In the Transplantation Settingsupporting
confidence: 55%
See 1 more Smart Citation
“…All patients were non-diabetic at the time of transplant, and all received equivalent numbers of islets (~5000 IE/kg). Using histological markers of β-cell identity including hormones, vimentin, synaptophysin, Ucn3, and MafA, we found that β-cell dedifferentiation was evident in all patients undergoing PIAT, which paralleled disease severity, and could be stratified relative to ND control and T2DM control donor samples [128]. These findings were further supported by pre-and postsurgical metabolic function tests, HbA 1C , and GSIS assessments with up to 4 years follow-up.…”
Section: Endocrine Cell Dedifferentiation In the Transplantation Settingsupporting
confidence: 55%
“…These findings were further supported by pre-and postsurgical metabolic function tests, HbA 1C , and GSIS assessments with up to 4 years follow-up. Results indicated that pre-surgical insulin resistance was associated with loss of β-cell phenotype, and hence function, at the time of surgery, and might suggest a possible pre-surgical tool which can inform transplant success [128]. These data further indicate that islet cell quality and maturity is paramount for long-term glucose homeostasis following transplantation.…”
Section: Endocrine Cell Dedifferentiation In the Transplantation Settingmentioning
confidence: 85%
“…Changes in islet cell identity, cell proliferation, and dedifferentiation can be induced by different types of trauma, including hyperglycemia 29 and pancreatitis. 15 , 30 No CGA+ve/insulin or glucagon negative cells were found in the explants, suggesting that endocrine neogenesis was not occurring. Transdifferentation and dedifferentiation of islet cells are associated with bihormonal expression of insulin and glucagon and appearance of vimentin in hormone-positive cells, respectively.…”
Section: Discussionmentioning
confidence: 97%
“… 21 OGTT was completed after a 12 h fast, with blood sampling at 0, 30, 60, 90, and 120 min. Fasting insulin (3−8 uIU/mL), proinsulin (2.5−8.8 pmol/L), and C-peptide (0.8−1.9 ng/mL) were measured as previously reported, 12 with glucose tested by automated chemistry analysis, C-peptide assayed by quantitative electrochemiluminescent immunoassay, and insulin and proinsulin assayed by quantitative chemiluminescent immunoassay. Reports suggest proinsulin >10 pmol/L is a marker of IR, 22 the proinsulin-to-insulin ratio >0.3 is a marker of β-cell distress independent of IR, 23 and elevated proinsulin-to-C-peptide ratio (PI/C) may be a superior marker of hyperproinsulinemia than insulin in predicting diabetes.…”
Section: Methodsmentioning
confidence: 99%
“… 9 Indeed, although it is logical and expected that insufficient transplanted islet mass has poorer glycemic outcomes, 10 , 11 achieving or even surpassing suggested transplanted islet number alone is still inadequate to guarantee insulin independence, and the role and methods of defining pretransplant islet function are critically required. We recently showed that CP itself contributes to islet identity loss 12 and is an independent variable from the clinical guideline of transplanting ≥5000 islet equivalents (IE) per kilogram body weight. 13 , 14 These results demonstrated that islet and β-cell–specific loss of identity was not exclusively related to pretransplant glucose levels, as all patients were nondiabetic at the time of surgery.…”
mentioning
confidence: 99%